Pharmacokinetic Simulation Analysis of Less Frequent Nivolumab and Pembrolizumab Dosing: Pharmacoeconomic Rationale for Dose Deescalation. (5th January 2022) - Peer, Cody J.; Heiss, Brian L.; Goldstein, Daniel A.; Goodell, Jennifer C.; Figg, William D.; Ratain, Mark J.
Abstract: Nivolumab and pembrolizumab, anti–programmed cell death protein 1 monoclonal antibodies, have revolutionized oncology but are expensive. Using an interventional pharmacoeconomic approach, these drugs can be administered less often to reduce costs and increase patient convenience while maintaining efficacy. Both drugs are good candidates for less frequent dosing because of long half‐lives and no evidence of a relationship of dose to efficacy. Established population pharmacokinetic models for both nivolumab and pembrolizumab were used to simulate profiles for multiple dosing regimens on 1000 randomly generated virtual patients. Simulations were initially performed on standard dose regimens to validate these in silico predictions. Next, simulations of nivolumab 0.3 mg/kg every 3 weeks revealed that >95% of patients maintained ≥1.5 μg/mL at steady state, which was inferred as the minimum effective concentration (MEC) for both drugs. Various alternative dosing regimens were simulated for both drugs to determine which regimen(s) can maintain this MEC in >95% of patients. Extended dosing regimens of nivolumab 240 mg every 4 weeks and 480 mg every 8 weeks along with pembrolizumab 200 mg every 6 weeks were simulated, showing that >95% of patients maintained MEC or greater. These simulations demonstrate the potential to reduce drug exposure by at least 50%, thus substantially reducing patient visits (as well as costs), while maintaining equivalent efficacy. These models provide the scientific justification for an ongoing prospective randomized clinical trial comparing standard interval fixed dosing with extended interval fixed dosing, and ultimately an efficacy‐driven comparative trial.